(untitled) (Ukrainian Journal of Ophthalmology, 2026)
To date, the problem of surgical treatment for keratoconus has not been solved completely. After corneal transplantation, high refractive errors (myopic astigmatism, as a rule) occur in a graft. This reduces visual outcomes of keratoplasty. Why is myopic refraction formed so persistently in the grafted cornea? Let us present our view of the problem.